Happiness at Work Melaui Strategic Talent Relationsip Management - Januari Ayu Fridayani (STIE Kertanegara Malang, 2022)
The concept of happiness at work will be a magnet for top talent to occupy pivotal positions. This is based on the phenomenon that the net generation is here with the slogan working to live which has an orientation about balance in life (work-life balance). But sometimes the older managers considers the concept to show a lack of commitment and loyalty at work, therefore the conventional approach is no longer relevant to the capacity of this generation. then the Human Capital Department must have the right strategy to manage it. This chapter will provide a systematic overview of Strategic Talent Relationship Management (STRM) for young future leaders, based on the concept of strategic talent management (Collings & Mellahi, 2009) and Talent Relationship Management (Trost, 2014) also Human Capital Department policies at Maybank Indonesia as an example of the implementation of one aspect that is in the STRM component. The basic principles will be discussed at the beginning of this chapter, followed by an overview of STRM componentKeywords: Happiness at work, Talent Management, Human Capital Strategic